Heart Rate Variability Duration: Expanding the Ability of Wearable Technology to Improve Outpatient Monitoring? - Sheridan, David C.; Domingo, Karyssa N.; Dehart, Ryan; Baker, Steven D. (Frontiers in Psychiatry, 2021)
Heart rate variability (HRV) evaluates beat-to-beat interval (BBI) differences and is a suggested marker of the autonomic nervous system with diagnostic/monitoring capabilities in mental health; especially parasympathetic measures. The standard duration for short-term HRV analysis ranges from 24 hours down to 5-minutes. However, wearable technology, mainly wrist devices, have large amounts of motion at times resulting in need for shorter duration of monitoring. The objective of this study was to evaluate the correlation between 1 minute and 5 minute segments of continuous HRV data collected simultaneously on the same patient. Subjects wore a patch electrocardiograph (Cardea Solo, Inc.) over a 1-7 day period. For every consecutive hour the patch was worn, we selected a 5-minute, artifact-free electrocardiogram segment. HRV metric calculation was performed to the entire 5-minute segment and the first 1-minute from this same 5-minute segment. There were 492 hours of electrocardiogram data collected allowing calculation of 492 5 minute and 1 minute segments. 1 minute segments of data showed good correlation to 5 minute segments in both time and frequency domains: root mean square of successive difference (RMSSD) (R=0.92), high frequency component (HF) (R=0.90), low frequency component (LF) (R=0.71), and standard deviation of NN intervals (SDNN) (R=0.63). Mental health research focused on parasympathetic HRV metrics, HF and RMSSD, may be accomplished through smaller time windows of recording, making wearable technology possible for monitoring.